Strength Development of Geopolymer Concrete Containing Palm Oil clinker Powder - Azlan, Nurul Isnani; Ismail, Amalina Hanani; Kusbiantoro, Andri (Progress in Engineering Application and Technology, 2022)
Manufacturing of cement is responsible for the high carbon dioxide (CO2) emission and leads to global warming. Therefore, geopolymer is introduced as an alternative binder to reduce CO2 emissions and utilize industrial by-products as primary materials. It is synthesis by activating the aluminosilicate materials with alkaline solutions. Meanwhile, palm oil clinker powder (POCP) is a good source of alumina and silica and is categorized as pozzolanic material but often overlooked due to its less reactivity trait. However, the reactivity of POCP can be enhanced by increasing its finesse. Therefore, this study utilizes POCP as blending binder materials in fly ash-based geopolymer concrete with different percentages of 0.0, 2.0, 4.0, 6.0, 8.0 and 10.0 % (by the weight of fly ash). Slump test was conducted to determine the workability of freshly mixed geopolymer concrete. Strength performance of fly ash-based geopolymer concrete was evaluated on 7 and 28 days of curing. Based on the findings, the slump of fly ash-based geopolymer concrete with no blended POCP recorded a higher value than with POCP. The inclusion of 6.0 % of POCP in geopolymer showed the highest compressive strength result with 54.97 MPa at 28 days of curing. Increasing POCP finesse significantly impacted the geopolymerisation process due to the rapid dissolution of aluminosilicates materials and producing polymerization products. Therefore, POCP is an excellent blending binder for fly ash-based geopolymer and sustainable source material for a greener product.